Metformin-loaded microsphere promotes an anti-tumour response through the caspase-mediated apoptotic pathway against MDA-MB-231 cells (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Metformin has been reported to have antidiabetic effects. Metformin also has anti-inflammatory and antibacterial activity. However, the target specificity remains the major problem regarding this. Therefore, as it lacks target specificity, nanoformulation or microsphere formulation of this compound might have a good chance of overcoming this problem. Thus, to overcome this problem, we have made a metformin-loaded microsphere that shows target-specific activity. Furthermore, the microsphere-loaded Metformin was administered to the EAC cell, MDA-MB-231. Results showed that the formulated drug was more potent against the MDA-MB-231 cell line. It shows dose-dependent inhibition in cell growth. For further evaluation, we investigated this matter and found that the drug-induced cytotoxicity is ROS-dependent and may occur through alterations in mitochondrial membrane potential. Additionally, this causes apoptotic marker proteins, such as cleaved PARP and cleaved caspase-3, to increase in expression. Overall, our data indicated that the formulated metformin was more effective than the free form in reducing cancer growth and enhancing survivability. Thus, the findings suggest that the formulated drug may be effective in reducing cancer growth and improving survivability.